2017
DOI: 10.1158/1078-0432.ccr-16-2540
|View full text |Cite
|
Sign up to set email alerts
|

Detecting the Presence and Progression of Premalignant Lung Lesions via Airway Gene Expression

Abstract: Lung cancer is the leading cause of cancer-related death in the United States. The molecular events preceding the onset of disease are poorly understood, and no effective tools exist to identify smokers with premalignant lesions (PMLs) that will progress to invasive cancer. Prior work identified molecular alterations in the smoke-exposed airway field of injury associated with lung cancer. Here, we focus on an earlier stage in the disease process leveraging the airway field of injury to study PMLs and its utili… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
48
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(54 citation statements)
references
References 56 publications
6
48
0
Order By: Relevance
“…On the other hand, less common drivers tended to occur preferentially early in specific tumour subtypes. When our results are compared to previously reported models of progression from pre-malignant to malignant lung cancer (based on sampling pre-malignant lesions) 54 , we find similar patterns.…”
Section: Discussionsupporting
confidence: 83%
“…On the other hand, less common drivers tended to occur preferentially early in specific tumour subtypes. When our results are compared to previously reported models of progression from pre-malignant to malignant lung cancer (based on sampling pre-malignant lesions) 54 , we find similar patterns.…”
Section: Discussionsupporting
confidence: 83%
“…In future, single‐cell transcriptomics may offer even greater value in understanding pre‐malignant lesions, where changes in gene expression are limited to a relatively small proportion of cells which may be too subtle to detect in bulk RNA sequencing. This has been demonstrated in pre‐malignant lung lesions among other cancers …”
Section: Discussionmentioning
confidence: 76%
“…In future, single-cell transcriptomics may offer even greater value in understanding pre-malignant lesions, where changes in gene expression are limited to a relatively small proportion of cells which may be too subtle to detect in bulk RNA sequencing. This has been demonstrated in pre-malignant lung lesions among other cancers 33. Relatively, few OPMDs will undergo MT, and clinical observation and histopathological assessment alone do not allow accurate prediction of which lesions will progress to malignancy.Exomic studies of OPMDs and their comparison with OSCC would allow an understanding of the process of oral carcinogenesis, in particular the accumulation and timing of specific mutations associated with malignancy.…”
mentioning
confidence: 99%
“…The Proliferative subtype is enriched with dysplastic PMLs from current smokers and is characterized by up-regulation of metabolic (OXPHOS/ETC/TCA) and cell cycle pathways and down-regulation of cilia-associated pathways. Previous work indicates increases in metabolic pathways in the airways of subjects with dysplastic lesions (13), in PMLs adjacent to LUSC tumor (24), and in smokers at high-risk for lung cancer (25) as well as increases in proliferation (via Ki67 levels, as mentioned above) that have been utilized as an endpoint in lung cancer chemoprevention (26,27). Identification of patients with Proliferative lesions may be useful to enrich lung cancer chemoprevention trials with high-risk subjects or to identify patients who would benefit from more frequent lung cancer screening.…”
Section: Discussionmentioning
confidence: 98%
“…Previously, we have shown that bronchial brushes from normal appearing areas of the mainstem bronchus could predict the presence of PMLs (13); however, that study lacked biopsies and brushes from the same subjects. Above, in both the DC and the VC biopsies, the Proliferative subtype, represents a distinct subtype of PMLs enriched for dysplastic histology expressing metabolic and proliferative pathways.…”
Section: Normal Appearing Airway Field Brushes Reflect Biopsy Moleculmentioning
confidence: 97%